Univerzitetna biblioteka v Ljubljani - Kodrič-Dačić, Eva (Knjižnica, 2005)
The Library of the University in Ljubljana moved into the new library building in 1941 at the very beginning of the Second World War. By 1943, when fascist Italy collapsed, the building was almost completely furnished. In January 1944, a German plane crashed into the building and the fire which broke out, destroyed the main reading room, numerous books and public catalogues. The authorities acted immediately and organized the reconstruction of the heavily damaged building, initiated an action for the replacement of library collections and employed workers for the creation of new catalogues. The library also had considerable support from the authorities regarding its national functions i.e. collecting legal deposit, acquiring patriotica, publishing the national bibliography, which led toward the affirmation of the Slovenian National Library.
Keywords: Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana; nacionalne knjižnice; 1943/1945; zgodovinski pregledi